All things paper : simple, elegant objects made with paper - Martin, Ann, 1954 July 5- (Tuttle Publishing, 2013)
"Ann Martin has searched the world over for unique and beautiful paper crafts to feature on her popular website--AllThingsPaper.net. In this new book, she gathers the best of these projects and shows you how to make them in a way that is simple and fun. All of the paper products in this book are designed by respected paper craft artists who have been making amazing things with paper for many years. Each of the projects has easy-to-follow instructions and detailed photos enabling you to create your own personal version in minutes. These colorful and impressive pieces include art objects to display at home as well as items which have practical uses. All of the pieces make a wonderful keepsake or a gift that expresses the beauty, elegance, and versatility of paper. Projects include: Candle Luminaries Citrus Slice Coasters Mysterious Stationery Box Everyday Tote Bag Silver Orb Pendant Fine Paper Yarn Necklace Wedding Cake Card Perfect Journey Journal "--